Morphology and multigene phylogeny reveal a new order and a new species of wood-inhabiting basidiomycete fungi (Agaricomycetes) - Luo, Kai-Yue; Zhao, Chang-Lin (Frontiers in Microbiology, 2022)
Dead wood-associated fungi play an important role in wood degradation and recycling of organic matter in the forest ecological system. Xenasmataceae is a cosmopolitan group of wood-rotting fungi that grows on tropical, subtropical, temperate, and boreal vegetations. In this study, a new fungal order Xenasmatales is introduced based on both morphology and multigene phylogeny to accommodate Xenasmataceae. According to the internal transcribed spacer and nuclear large subunit (ITS+nLSU) and nLSU-only analyses of 13 orders, Xenasmatales formed a single lineage and then grouped with orders Atheliales, Boletales, and Hymenochaetales. The ITS dataset revealed that the new taxon Xenasmatella nigroidea clustered into Xenasmatella, and closely grouped with Xenasmatella vaga. In the present study, Xenasmatella nigroidea collected from Southern China is proposed as a new taxon, based on a combination of morphology and phylogeny. Additionally, a key to the Xenasmatella worldwide is provided.